Mechanisms of angina in patients with biopsy-proven viral myocarditis: insights from intracoronary acetylcholine testing. (25th November 2020) - Seitz, A; Martinez Pereyra, V; Hubert, A; Klingel, K; Bekeredjian, R; Sechtem, U; Ong, P
Abstract: Background: Patients with myocarditis often present with angina pectoris despite unobstructed coronary arteries. The underlying pathophysiological mechanism of angina in these patients remains to be elucidated. Coronary artery spasm is a well-known cause of angina in patients with unobstructed coronary arteries. In this study, we sought to assess the frequency of coronary vasomotor disorders in patients with biopsy-proven viral myocarditis. Methods: In total, 700 consecutive patients who underwent endomyocardial biopsy for suspected myocarditis between 2008 and 2018 were retrospectively screened. Of these patients, viral myocarditis was confirmed in 303 patients defined as histological/immunohistological evidence of myocardial inflammation and presence of viral genome confirmed by PCR. Of these patients, 34 patients had angina despite unobstructed coronary arteries and underwent intracoronary acetylcholine (ACh) provocation testing in search of coronary spasm. Epicardial spasm was defined as acetylcholine-induced reproduction of the patient's symptoms associated with ischemic ECG changes and >90% epicardial vasoconstriction. Microvascular spasm was defined as symptom reproduction and ECG changes in the absence of significant epicardial vasoconstriction. Results: Patients were 49±16 years old, 62% were male and left ventricular ejection fraction was 54±16%. Most frequent viruses were parvovirus B19 (PVB19, 59%) and human herpes virus 6 (HHV6, 26%), 2 patients had combined PVB19/HHV6 infection and 3 patients other herpesviruses (CMV, EBV, VZV). Epicardial spasm was observed in 10 patients (29%) during ACh testing and microvascular spasm was found in 11 patients (32%). The rate of coronary spasm (epicardial and microvascular) was higher in the PVB19 subgroup compared to HHV6 (80% vs. 33%, p=0.031). In particular, there was a higher prevalence of microvascular spasm in PVB19 compared to HHV6 (45% vs. 0%, p=0.018). Conclusion: We observed a high prevalence of microvascular and epicardial spasm in patients with biopsy-proven viral myocarditis suggesting coronary spasm as a potential underlying mechanism for angina in these patients. Microvascular spasm was most often observed in patients with PVB19-associated myocarditis. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Robert-Bosch-Stiftung; Berthold-Leibinger-Stiftung